The Phenomenon of People Smuggling in the Lens of Indonesian Immigration: Efforts for Handling and Collaborating with Institutions in Handling it - Hana Farah Dhiba (Journal of Law and Border Protection, 2019)
People Smuggling or also known as human smuggling is a crime against humanity that is increasingly happening. Indonesia is one of the countries with a high number of people smuggling crimes and it is very potential. The phenomenon of People smuggling in Indonesia is closely related to immigration. This is because the crime of people smuggling involves immigration factors including traffic entering and leaving Indonesia, foreign citizens, Indonesian citizens and State sovereignty. Therefore, the importance of law enforcement and optimal eradication efforts need to be done by realizing various collaborations between institutions and between ministries so that people smuggling crime practices in Indonesia can be suppressed and minimized for the realization of national and state security guarantees. The research method used is descriptive qualitative research and normative juridical approach. From the research results, it can be seen that the People Smuggling Crime is a transnational crime that threatens the country from two sides, from outside and inside. From the outside, human smuggling is carried out by illegal foreign immigrants who make Indonesia a transit area. Meanwhile, the internal threat is the practice of people smuggling carried out by Indonesian citizens who want to work as Migrant Workers abroad through illegal channels or also known as Non-Porsedural TKI or Illegal Migrant Workers (TMI). With these two threats, it is necessary to pay more attention to eradicating these crimes. The implementation of cooperation between institutions is one of the answers to existing problems.